Effects of task type on spontaneous alternations of attentional states. - Weber, Mark; Cunningham, Emily; Beck, Diane M.; Sadaghiani, Sepideh; Wang, Ranxiao Frances (Memory & Cognition, 2024)
Mind wandering is a common occurrence that can have serious consequences, but estimating when mind wandering occurs is a challenging research question. Previous research has shown that during meditation, people may spontaneously alternate between task-oriented and mind-wandering states without awareness (Zukosky & Wang, 2021, Cognition, 212, Article 104689). However, under what conditions such alternations occur is not clear. The present study examined the effects of task type on spontaneous alternations between task focus and mind wandering. In addition to a meditation task, participants performed either a scene-categorization-based CPT or a visual detection task while attentional orientation was assessed via self-monitoring and intermittent probes. The three tasks differ in the extent of their reliance on continuous monitoring (less required in the detection than meditation and CPT tasks) and attentional orientation (oriented internally in meditation task and externally in CPT and detection tasks). To overcome prior methodological challenges, we applied a technique designed to detect spontaneous alternations between focused and mind-wandering states without awareness, based on how the proportion of "focused" responses/ratings to intermittent probes changes during a focus-to-mind-wandering interval (i.e., the period from one self-report of mind wandering to the subsequent self-report). Our results showed that the proportion of "focused" responses to intermittent probes remained constant with increasing interprobe interval during meditation (consistent with previous work), but declined significantly in the CPT and detection tasks. These findings support the hypothesis that spontaneous alternations of attentional states without self-awareness occur during tasks emphasizing internally but not externally oriented attention.